Should We Trust the Empirical Evidence from Present Value Models of the Current Account? - Benoît Mercereau; Jacques Alain Miniane (Kiel Institute for the World Economy (IfW), 2008)
The present value model of the current account has been very popular, as it provides an optimal benchmark to which actual current account series have often been compared. We show why persistence in observed current account data makes the estimated optimal series very sensitive to small-sample estimation error, making it close to impossible to determine whether the paths of the two series truly bear any relation to each other. Moreover, the standard Wald test of the model will falsely accept or reject the model with substantial probability. Monte Carlo simulations and estimations using annual and quarterly data from five OECD countries strongly support our predictions. In particular, we conclude that two important consensus results in the literature – that the optimal series is highly correlated with the actual series, but substantially less volatile – are not statistically robust.
Keywords: C52; C11; F41; F32; 330; Current account; present value model; model evaluation; Leistungsbilanz; Zeitreihenanalyse; Zeitpräferenz; Dynamische Investitionsrechnung; Theorie; OECD-Staaten